2002
DOI: 10.1109/tmi.2002.800585
|View full text |Cite
|
Sign up to set email alerts
|

Regional lung perfusion as determined by electrical impedance tomography in comparison with electron beam CT imaging

Abstract: The aim of the experiments was to check the feasibility of pulmonary perfusion imaging by functional electrical impedance tomography (EIT) and to compare the EIT findings with electron beam computed tomography (EBCT) scans. In three pigs, a Swan-Ganz catheter was positioned in a pulmonary artery branch and hypertonic saline solution or a radiographic contrast agent were administered as boli through the distal or proximal openings of the catheter. During the administration through the proximal opening, the ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 18 publications
(20 reference statements)
2
140
0
5
Order By: Relevance
“…In 1992 Brown et al [2] applied an isotonic 0.9% NaCl solution. About 10 years later the first usage of a hypertonic 1molar (5.8%) NaCl solution in animals was published [3]. This approach was later on used in animal experiments in view of estimation of local ventilation and perfusion distribution (V˙/Q˙ ratio) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 1992 Brown et al [2] applied an isotonic 0.9% NaCl solution. About 10 years later the first usage of a hypertonic 1molar (5.8%) NaCl solution in animals was published [3]. This approach was later on used in animal experiments in view of estimation of local ventilation and perfusion distribution (V˙/Q˙ ratio) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The ACT3 system (Edic et al 1995) has also been used extensively to image ventilation and perfusion in human subjects. Cross-sectional images of cardiac activity using the ACT3 system (Edic et al 1995) and the NOSER reconstruction algorithm (Cheney et al 1990) can be found in Cheney et al 1999. Other investigations of the feasibility and reproducibility of using EIT to image cardiac activity include Vonk Noordegraaf et al (1996,1997,1998), Hoetink et al 2002, Mueller et al 2001, Smit et al 2003, Frerichs et al 2002 The reader is referred to Borcea (2002) or Mueller and Siltanen (2003) for a discussion of existing reconstruction algorithms for EIT.…”
Section: Introductionmentioning
confidence: 99%
“…STFT benefits from the high temporal resolution provided by EIT and is capable of giving stable and robust time-averaged respiratory rate estimates and hence a reliable apnea alarm. In this way, there is no need for holding the breath like previous conventional methods performing the measurements [5,11]. The STFT is also simple to implement and benefits from the high computational efficiency of the Fast Fourier Transform (FFT) algorithm.…”
Section: Resultsmentioning
confidence: 99%